HIV and metaphor: an imaginative response to illness - Cardo, Julia Claire (Rhodes University, Faculty of Humanities, Department of Psychology, 1998)
The medical model has been criticised for its failure to attend to individuals' experience of illness and the meaning they attribute to illness. HIV / AIDS has challenged its adequacy and brought the question of meaning in illness into sharp focus. This study aimed to understand what it means to live with HIV by exploring the fantasies, images and metaphors that make up the depth of such an experience. Phenomenology was deemed the appropriate approach, as it assigns epistemological significance to metaphor and ontological primacy to the lifeworld. An interview guide was fashioned from existing phenomenological literature and in-depth interviews were conducted with eight HIV -infected individuals. Five protocols were selected to constitute the study. In addition, an audio tape recording of one individual's metaphorical dialogue with HIV was obtained and transcribed. The three protocols with the richest content of imagery and metaphor were subjected to phenomenological explication. The remaining two protocols were used to support and clarify emergent meaning. A phenomenological explication of the data revealed a number of salient metaphors and themes. Upon being diagnosed with HIV, individuals were confronted with a socially and institutionally prescribed understanding of the disease; HIV as synonymous with AIDS and immediate death, HIV as sexual deviance, and HIV as myth. These metaphors influenced their conceptualisation and handling of HIV. Individual embodied metaphors included: embodying a heart of stone to live with HIV and perceiving HIV as a punishment from God, a demon from the Devil, a death sentence and a torture. Affectively, the experience of HIV was constituted as fear of physical disfigurement and exposure, anxiety, vulnerability, anger, betrayal, injustice and isolation. In a process of resolution and transformation, individuals imbibed positive metaphors with which to continue living with HIV. In order to cope with HIV, individuals seemed to negotiate a metaphorical space in which to dwell with their virus. This entailed establishing some form of dialogue with HIV or a Higher Power. This study revealed that metaphorical thinking about HIV /AIDS has a powerful impact on individuals' embodiment of their world. Metaphor is also an effective means Clf conveying and eliciting meaning in the experience of illness. Based upon these findings, it was suggested that metaphor be a prime focus for future research endeavours.
Keywords: HIV infections; Metaphor -- Psychological aspects; Imagery (Psychology) -- Therapeutic use